Uma proposta de análise do coping no contexto de grupo de mães de bebês prematuros e com baixo peso na unidade de terapia intensiva neonatal - Ramos, Fabiana Pinheiro (2012)
The Motivational Theory of Coping defines coping as the process of self-regulation of behavior, emotion and motivational orientation in conditions of psychological stress, in order to maintain, restore or repair basic psychological needs of relatedness, competence and autonomy. Stressors may be perceived as a threat or challenge and coping is parsed into 12 "families", which represent the highest level of the hierarchical structure of coping, according to its adaptive outcome: (a) positive - self-reliance, support seeking, problem solving, information seeking, accommodation and negotiation; and (b) negative - delegation, isolation, helplessness, escape, submission and opposition. This approach was applied in the analysis of coping of the hospitalization of a newborn admitted to the Neonatal Intensive Care Unit (NICU) for preterm birth and/or low birth weight (PT–LW) in the context of a Group of Mothers (GM) in a public hospital. The participants were approached in the hospital and, after the research procedures explanation, they gave their written consent. Neonatal variables were collected on the Baby Form and 25 mothers comprised a convenience sample, and filled: (a) General Data Registration Protocol; (b) Brazil Criterion of Economic Classification; (c) The Ways of Coping Checklist (Brazilian version - EMEP); and (d) The Moment of the News Questionnaire. Then, they participated in one of the seven GM (2-7 participants), with brief and structured methodology and comprising: Session 1 - Characteristics of the baby and the NICU - with a Intervention Assessment Questionnaire (IAQ); and Session 2 - Child development and care following hospital discharge - with Book of Support to Intervention, IAQ, a User Satisfaction Inventory and an individual interview about coping. Three trained observers filled in: (a) Session Registration Protocol; (b) Protocol for Evaluation of Verbal and Nonverbal Behavior of Mothers in a Group Situation; and (c) Observation Instrument of the Mediator's Interaction Pattern in a Group Situation. During follow up after hospital discharge, mothers were interviewed and completed the Vital Events Scale and EMEP. The analyses of the coping process showed that the moment of the news of hospitalization and the first visit to the NICU caused great emotional impact, with reactions of sadness, worry, fear and surprise, shared by the parents. The coping strategies most frequently used during hospitalization belonged to families of coping self-reliance, negotiation andaccommodation (mediated primarily by religious belief) and support seeking (especially from husband/partner), perceiving the situation as a challenge and source of personal growth; but less adaptive strategies, such as delegation, also occurred. There were significant correlations between: (a) higher socioeconomic level and use of strategies related to the need for relatedness, (b) multiparous mothers and helplessness, escape and opposition and coping strategies grouped as perception of threat, (c) mothers who were not working out of home and self-reliance, and (d) greatest number of days of baby's hospitalization and less delegation. After hospital discharge, most did not report having difficulties with the babies, presenting higher average of negotiation, self-reliance, accommodation and seeking support and a significant reduction of delegation. Two mothers faced the loss of their children differently: with self-reliance and problem solving, and the other with negotiation and self-reliance, but both of them relied on religion. The GM had good adherence and positive evaluation due to learning, psychological support offered and exchange of experiences among mothers who reported feeling better after the sessions. The mediator of the GM followed the criteria for promoting coping, especially in providing structure (a predictable, consistent and contingent context). The data suggest that GM has helped promote the coping of these mothers when changing their perception of control and social support, and enhancing the satisfaction of their needs for competence and relatedness. This research presented the workability of the 12 families of coping system for the analysis of coping in adults, provided theoretical and methodological contributions to the study of coping, and broadened knowledge about the central theme by identifying and analyzing the coping strategies used by mothers in relation to the stressor – hospitalization in the NICU of PT–LW newborn's – on several occasions, mapping the process of coping with these mothers. Additionally, it has shown the importance of brief interventions in Pediatric Psychology, enabling coping promotion. It is expected that improvements in the coping process generated by the participation of the mothers in this research may have had, in the long term, positive results in their physical and mental health, and, cumulatively, in the course of their babies’ development.